ANALISIS UNSUR INTRINSIK DALAM NOVEL MARIPOSA KARYA LULUK HF DAN RELEVANSINYA SEBAGAI BAHAN AJAR TEKS CERITA FIKSI DI KELAS VIII SMP NEGERI 8 MEDAN - Marissa Valerina Pardosi, Novia; Januarsyah Daulay, Muhammad Anggie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe in depth the structure of intrinsic elements contained in the novel Mariposa by Luluk HF and analyze its relevance as an alternative teaching material for fictional story texts in class VIII of SMP Negeri 8 Medan. The research method applied in this study is a qualitative method using a descriptive approach. The main data source in this study is the text of the novel Mariposa by Luluk HF published by Coconut Books in 2018. Data collection techniques used include careful reading and note-taking techniques and documentation techniques, which are then analyzed through the stages of identification, classification, interpretation, and description of the data. The results show that the novel Mariposa has very complete and intact intrinsic elements, including the theme of the struggle for love and ideals, strong characters and characterization, a coherent progressive plot, a realistic setting, a third-person point of view, an educational message, and a communicative language style. Furthermore, this novel is considered very relevant to be used as teaching material for fictional story texts because it meets the Learning Outcomes of the Independent Curriculum, the simplicity of linguistic aspects, the closeness of the theme to adolescent life, and contains character education values.